Modeling final driving test system for JPJ using mobile technology - Mohd Muhaiyuddin, Nadia Diyana; Hussain, Azham (2006)
There is still lack of study in the area of e-government services for mobile application in Malaysia currently even though it is part of Vision 2020. Hence, more study is needed to provide guideline in developing a mobile application in Malaysia.Thus, this study will focused on JPJ Final Driving Test process and investigate the actual situation of this services from initial process until the end. The documentation will be based on UML notations which including use case diagram, requirement list and class diagram. The result of this research is produce a requirement model and relevance interface prototype features for developing e-government services especially converting from a paper form service into paperless application.